Anchored Pd-complexes in mesoporous supports: synthesis, characterization and catalysis studies for carbonylation reactions - Sarkar, Bibhas R.; Chaudhari, Raghunath V. (Catalysis Today, 2012)
Pd(pyca)(PPh3)(OTs) [pyca = 2-picolinate] complex is efficiently anchored inside different mesoporous matrices, such as MCM-41, MCM-48, SBA-15 using a molecular aminopropyl tether moiety employing different synthesis strategies. Thorough characterization of the materials using powder XRD, multinuclear (C-13, Si-29, P-31) CP-MAS NMR, XPS, SEM, N-2-sorption studies etc. confirmed the successful anchoring of the palladium complex to the walls of the support matrices thus establishing the synthesis protocols unambiguously. The catalysts were found to be highly active and selective for the carbonylation of different aryl olefins and alcohols. Consecutive recycling and successful reuse proved the stability and true heterogeneous nature of all the anchored catalysts, which is a substantial advancement over the existing heterogeneous catalysts for carbonylation. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Anchored catalysts; Carbonylation; Immobilization; mesoporous materials; Palladium complex